A faunal summary of Simulium (Montisimulium) with descriptions of five new species from China (Diptera: Simuliidae) - Han-Bin, Chen; Guo-Sheng, Lian; Chun-Lin, Zhang (Zootaxa, 2011)
This paper provides the first checklist of the subgenus Montisimulium Rubtsov, 1974 of genus Simulium from China, which lists 24 Chinese species including 19 known species and 5 new species, S. (M.) xinzhouense sp. nov., S. (M.) polyprominulum sp. nov., S. (M.) schizostylum sp. nov., S. (M.) luliangense sp. nov. and S. (M.) wulaofengense sp. nov., were collected from Shanxi Province, China. Keys to the species of S. (Montisimulium) known to occur in China are also provided.